Operational Research in the Era of Digital Transformation and Business Analytics BALCOR 2020, Thessaloniki, Greece, September 30-October 3, 2020 - Matsatsinis, Nikolaos F.; Kitsios, Fotis C.; Madas, Michael A.; Kamariotou, Maria I. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This proceedings volume presents new methods and applications in Operational Research and Management Science with a special focus on Business Analytics. Featuring selected contributions from the XIV Balkan Conference on Operational Research held in Thessaloniki, Greece in 2020 (BALCOR 2020), it addresses applications and methodological tools or techniques in various areas of Operational Research, such as agent-based modelling, big data and business analytics, data envelopment analysis, data mining, decision support systems, fuzzy systems, game theory, heuristics, metaheuristics and nature inspired optimization algorithms, linear and nonlinear programming, machine learning, multiple criteria decision analysis, network design and optimization, queuing theory, simulation and statistics. .
Keywords: Operations research; Management science; Quantitative research; Operations Research and Decision Theory; Operations Research, Management Science .; Data Analysis and Big Data